2014
DOI: 10.1080/14786419.2014.955486
|View full text |Cite
|
Sign up to set email alerts
|

Antiphytopathogenic activity ofPsoralea glandulosa(Fabaceae) againstBotrytis cinereaandPhytophthora cinnamomi

Abstract: The resinous exudate, three meroterpenes, namely bakuchiol (1), 3-hydroxybakuchiol (2), 12-hydroxyisobakuchiol (3), and one furanocoumarin, psoralen (4), were isolated from the leaves of culen (Psoralea glandulosa). In addition to these, two semi-synthetic derivatives, bakuchiol acetate (5) and bakuchiol methyl eter (6), were obtained from 1, and were subsequently evaluated in vitro for the inhibitory effect of resin and compounds on the mycelial growth of Botrytis cinerea Pers.: Fr. and Phytophthora cinnamomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…A modified Folin-Ciocalteu (FC) method ( Madrid et al., 2015 ) was used. The sample solution (15 μ L) was mixed with distilled water (15 μ L) and 0.2 N FC reagent (150 μ L).…”
Section: Methodsmentioning
confidence: 99%
“…A modified Folin-Ciocalteu (FC) method ( Madrid et al., 2015 ) was used. The sample solution (15 μ L) was mixed with distilled water (15 μ L) and 0.2 N FC reagent (150 μ L).…”
Section: Methodsmentioning
confidence: 99%
“…Mycelial discs (4 mm in diameter) of test fungi grown on rye B agar [ 38 ] were cut from the margins of the colony and placed on the same medium containing different concentrations of the test oxyalkyl chalcones (12.5–400 µg/mL). After incubation at 20 °C for seven days, radial mycelial growth was measured and was compared with the controls [ 39 ]. Control plates were treated with difenoconazole and metalaxil.…”
Section: Methodsmentioning
confidence: 99%
“…Chiang et al found that psoralen displayed an antibacterial effect on mycobacterium tuberculosis H37Rv ( Chiang et al, 2010 ). Villegas observed that psoralen inhibited the growth of P. cinnamomi mycelia ( Villegas et al, 2015 ), indicating that psoralen has the potential to be a biological pesticide. Li et al found that psoralen inhibited the formation of biofilms, eliminated established biofilms and reduced their viability ( Li et al, 2018 ).…”
Section: Antiviral and Antibacterial Effects Of Psoralenmentioning
confidence: 99%